Contrasting effects of linezolid on healthy and dysfunctional human neutrophils: reducing C5a-induced injury - Stephen Evans (Scientific Reports, 2020)
Background: To manage increasing demand for emergency and unscheduled care NHS England policy haspromoted services in which patients presenting to Emergency Departments (EDs) with non-urgent problems aredirected to general practitioners (GPs) and other primary care clinicians working within or alongside emergencydepartments. However, the ways that hospitals have implemented primary care services in EDs are varied. The aimof this study was to describe ED clinical leads’ experiences of implementing and delivering ‘primary care services’and ‘emergency medicine services’ where GPs were integrated into the ED team. Methods: We conducted interviews with ED clinical leads in England (n = 19) and Wales (n = 2). We usedframework analysis to analyse interview transcripts and explore differences across ‘primary care services’, ‘emergency medicine services’ and emergency departments without primary care services. Results: In EDs with separate primary care services, success was reported when having a distinct workforce ofprimary care clinicians, who improved waiting times and flow by seeing primary care-type patients in a timely way,using fewer investigations, and enabling ED doctors to focus on more acutely unwell patients. Some challengeswere: trying to align their service with the policy guidance, inconsistent demand for primary care, accessiblecommunity primary care services, difficulties in recruiting GPs, lack of funding, difficulties in agreeing governanceprotocols and establishing effective streaming pathways. Where GPs were integrated into an ED workforce successwas reported as managing the demand for both emergency and primary care and reducing admissions